EFEKTIVITAS SISTEM MANAJEMEN INFORMASI KEPEGAWAIAN - Seno Andri, Desi Andarwati, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Effectiveness of Staffing Management Information Systems. The purpose of this study was to determine the effectiveness of SIMPEG in Pekanbaru City BKPSDM and find out the inhibiting factors. This study uses a qualitative descriptive research method approach. Primary data is obtained directly through interviews from key informants, namely the Head of BKPSDM, Secretary of BKPSDM and BKPSDM Staff. Secondary data obtained from research documents. Data analysis through stages, starting from data collection, data reduction, data presentation and conclusion drawing. The results showed that the effectiveness of the Civil Service Information System (SIMPEG) in the Human Resources Development and Human Resources Agency of the City of Pekanbaru was influenced by input, process and output. Information technology elements cannot be released in relation to the implementation of SIMPEG. Synergy between technology and its implementation by employees can be seen from the implementation of procedures and system workflow processes which include input subsystems, process sub-systems and output sub-systems.